Semper Fi: The Corps Series #1 - Griffin, W. E. B. (New York : Jove Books, 1986)
Marine Kenneth McCoy works as a spy in China and the United States in order to avert a looming threat from the Japanese in 1941.
Keywords: United States -- Marine Corps -- Fiction -- History -- 20th century; United States -- Marine Corps -- Fiction; United States -- Fiction -- Military history; Historical fiction; War stories; Spy stories